Potential Epigenetic Regulation in the Germinal Center Reaction of Lymphoid Tissues in HIV/SIV Infection - Wang, Xiaolei; Xu, Huanbin (Frontiers in Immunology, 2018)
The production of high-affinity and broadly neutralizing antibodies (bnAbs) plays a key role in the defense against pathogens. These antibody responses require effective germinal center (GC) reaction within anatomical niches of GCs, where follicular T (Tfh) cells provide cognate help to B cells for T cell-dependent antibody responses. Emerging evidences indicate that GC reaction in normal state and perhaps establishment of latent Tfh cell reservoir in HIV/SIV infection are tightly regulated by epigenetic histone modifications, which are responsible for activating or silencing chromatin. A better understanding of the mechanisms behind GC responses, at cellular and molecular levels, thus provides necessary knowledge for vaccination and immunotherapy. In this review, we discussed the epigenetic regulation of germinal center responses, especially for GC B and Tfh cell under normal state or HIV/SIV infection.